Pelatihan Pembuatan dan Pemasaran Kerajinan Seni Barongan Di Desa Kalikejambon - Wahyudi, Wahyudi; Sari, Ayu Titis Rukmana; Qathafi, Agil Muamar (Universitas Nusantara PGRI Kediri, 2021)
Barongan arts craft training is motivated by the lack of employment opportunities in Dusun Sawen, Kalikejambon Village, so that the community does not have an income that is considered decent. However, in the hamlet there is a youth group association called the Sawen Youth Association or called PERKASA which has activities in the arts. So far there has been no activity program from the PERKASA youth group that can provide them with additional income, so this training is an alternative to being able to train entrepreneurship in groups. This training consists of 5 stages, namely (1) training for making masks (2) training for making jamang (3) training for making ornaments (4) training in marketing (marketplace) (5) training for management of community organizations. The goal is to preserve the skills of making barongan arts crafts for children's toys, increasing the economic income of the community. Through marketplace training, the market share of barongan arts is getting wider. The establishment of 5 marketing accounts in the marketplace and social media, namely creative KJP (Shopee), creative KJP (Tokopedia), creative KJP (Facebook), creative KJP (Instagram) and WhatsApp, as well as a website that can be accessed on the link: https: // www .kjpkjual.com. Offline marketing is done by filling the booths at the souvenir center in Jombang. The formation of the creative KJP group as a forum for the management and development of the barongan mask craft business. Through this training the community becomes more skilled in making barongan art crafts, can market these products through the online